Gambaran Pengasuhan Anak (0-2 Tahun) oleh Ibu yang Tinggal di Rumah Tahanan Negara Kelas I Makassar - Nur Indriani; M. Daud (Indonesian Journal of Pedagogical and Social Sciences, 2022)
Abstract: It is unusual for a mother to have to serve a period of detention with her infant child in the Detention Center for violating the law. Thus a mother takes care of her child in the Detention Center without being accompanied by a father. This study aims to determine the description of the parenting of mothers who live in Makassar Class I State Detention Center. Respondents in this study were 2 mothers who lived with their children in Makassar Class I State Detention Center. The research method used in this study is a qualitative method using a case study approach. The results showed that there are several obstacles in caring for children at the Makassar State Detention Center in meeting the needs of their children, including physical needs and the needs of the child’s social environment. Meanwhile, in meeting the psychological needs of children, respondents fulfil the need for security and provide affection for children aged 0-2 years by mothers with the status of correctional inmates who live in Makassar Class I State Detention Center. Keywords: Description of parenting, Detention Center, Mothers.